PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT The Univenus, Kragilan Serang Tahun 2018) - Adistri Novita Lestari; Emma Suryani (Tirtayasa Ekonomika, 2018)
This study aims to determine the effect of effect of transformasional leadership style and ogranizational culture on employee performance through job satisfaction as intervening variable. Determination of samples used slovin formula and obtained a sample of  75 respondents using quantitative data analysis methods.From result of calculation of SPSS v.22, result of research with significance level of 0,05% obtained conclusion: (1) there is a positive and significant influence of transformasional leadership style to employee performance (2) there is a positive and significant influence of organizational culture toward employee performance (3) there is a positive and significant influence of transformasional leadership style to job satisfaction (4) there is a positive and significant influence of organizational culture on job satisfaction (5) there is positive and significant influence of  job satisfaction toward employee performance obtained (6) the job satisfaction variable gives a not mediation but significant effect of transformasional leadership style to employee performance (7) the job satisfaction variable gives a not mediation but significant effect of the organizational culture to employee performance Keywords: Transformasional Leadership Style, Organizational Culture, Employee Performance, and Job Satisfaction